Teori Penemuan Hukum Islam: Pendekatan Bayani, Ta‘līl, dan Istislāḥī dalam Kerangka Ijtihad Kontemporer: The Theory of Islamic Legal Discovery: Bayani, Ta‘līl, and Istislāḥī Approaches within the Framework of Contemporary Ijtihād - Muh. Fadel As'ad; Ahmad Musyahid; Lomba Sultan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The discovery of Islamic law is an epistemological process that involves the interaction between divine revelation and human reasoning in responding to legal challenges. This study examines three primary approaches in the philosophy of Islamic legal discovery: the Bayani theory, the Ta‘līl theory, and the Istislāḥī theory. The Bayani theory relies on the authority of textual language and its linguistic structure as the foundation of legal derivation. The Ta‘līl theory emphasizes the identification of the ‘illah (effective cause) as the rational basis behind legal rulings. Meanwhile, the Istislāḥī theory is oriented toward achieving public interest (maṣlaḥah) and the objectives of Islamic law (maqāṣid al-sharī‘ah) in formulating context-sensitive legal norms. This research employs a qualitative approach through literature analysis of classical works such as Al-Risālah, Al-Mustasfā, and Al-Muwāfaqāt, complemented by contemporary scholarship including Hashim Kamali, Wael B. Hallaq, and Jasser Auda. The findings suggest that these three theories are not mutually exclusive; rather, they complement one another in forming a comprehensive methodology of legal discovery. In today’s context, the integration of these approaches is essential to generate legal reasoning that is both responsive to socio-legal realities and firmly rooted in the principles of Islamic law. Thus, the philosophy of legal discovery in Islam offers a framework that is not only textual and rational, but also transformative in addressing the demands of modern times.